MNC Otomotif di Tengah Persaingan Industri (Studi Kasus: Upaya Toyota Mempertahankan Dominasi di Indonesia) - Sonbai, Angelique Camelita Korassa; Wiranata, I Made Anom; Priadarsini, Ni Wayan Rainy (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 4 No 4 (2025): JURNAL DIKSHI, 2025)
One sector that significantly impacts the Indonesian economy is the automotive industry. The Indonesian government strongly supports the development of the automotive industry in Indonesia because the automotive industry can produce a positive impact on Indonesia's economic growth. Automotive companies in Indonesia take advantage of Indonesia's positive response by increasing product innovation and intensively utilizing technology. Toyota is a Japanese automotive company that has dominated the Indonesian automotive sector for decades. Toyota as a company that has already dominated experienced dominance disruption with the emergence of new automotive companies and the many innovations offered by these companies. This study aims to describe the efforts made by Toyota to maintain its dominance in Indonesia. This research uses a descriptive-qualitative method using the perspective of interdependence liberalism to see Toyota's efforts to enter the Indonesian automotive market and the perspective of industrial competition, Toyota's efforts to obtain consumer preferences amid industrial competition. This research finds several efforts made by Toyota to maintain its dominance in the Indonesian automotive market. Toyota invests, collaborates with SOEs, and contributes to society and the environment to enter the Indonesian automotive market. In addition, Toyota also innovates on the products produced, diversifies the products produced, and improves the quality of after-sales service offered to consumers. Keywords : Dominance , Economic Interdependence, Industry Competition , National Automotive , Toyota.